4x+6=8x-14

Simple and best practice solution for 4x+6=8x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+6=8x-14 equation:


Simplifying
4x + 6 = 8x + -14

Reorder the terms:
6 + 4x = 8x + -14

Reorder the terms:
6 + 4x = -14 + 8x

Solving
6 + 4x = -14 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
6 + 4x + -8x = -14 + 8x + -8x

Combine like terms: 4x + -8x = -4x
6 + -4x = -14 + 8x + -8x

Combine like terms: 8x + -8x = 0
6 + -4x = -14 + 0
6 + -4x = -14

Add '-6' to each side of the equation.
6 + -6 + -4x = -14 + -6

Combine like terms: 6 + -6 = 0
0 + -4x = -14 + -6
-4x = -14 + -6

Combine like terms: -14 + -6 = -20
-4x = -20

Divide each side by '-4'.
x = 5

Simplifying
x = 5

See similar equations:

| -9x-13=-4x+32 | | (x)(2x)(4x^2)=2048 | | 10x-28=92 | | (x)(2x)(4x^2)=256 | | x^4=256 | | 2x-14=-2x+18 | | 5x+22=7x+38 | | 9x-14=6x+19 | | 7.3y-5.81=-51.9 | | -4+2.2h=3.7 | | -17=-5k-2 | | 5+3+9=57 | | 3*x^2+6*xy+y^2+8*x+2*y-5=0 | | y(x^2-5)=X^3-4x^4 | | 5c-8=3c-2 | | 6x-5=2x-4 | | y=(3x^5+8)(x^2) | | 72-3x=15x+16 | | 10-8x=95-43x | | 4.125c+5=-9.85 | | -1.7w-4=2.63 | | 4x+7=-19-9x | | -3.3+6.5=1.55 | | 10.7w+4=47.87 | | 9x+7=6x | | 6.2x+3.7=22.3 | | 6x+16=14x-80 | | 9x-(4x-3)=11+2(2x-7) | | 36*x+5= | | 36*36= | | 0.3(0.2x+1)=0.4(0.5x-1) | | 6.5Y-15=4Y+3.4 |

Equations solver categories